KLASIFIKASI CITRA X-RAY COVID-19 DENGAN MODEL CONVOLUTIONAL NEURAL NETWORKS ALGORITHMA LOGISTIC REGRETION - Gunawan Budi Sulistyo; Pudji Widodo - Universitas Bina Sarana Informatika (Indonesian Journal of Networking and Security (IJNS), 2022)
Abstract - Covid-19 (Corona Virus Disease) a new infectious outbreak originating from Wuhan in 2019. To find out how to diagnose COVID-19 is to analyze X-ray images of the lungs. Medical experts analyze the x-ray images of the lungs to determine the diagnosis, whether it is Covid or normal. This is very time consuming and inefficient. Therefore, technology is needed that can quickly diagnose the disease. Convolutional Neural Network (CNN) with Logistic Regression algorithm is one of the developments of the Multilayer Perceptron (MLP) algorithm which is designed to identify various image patterns from various sides. The CNN model built in this study has 200 convolution layers with ReLU activation functions, Batch Normalization, and 5 max-pooling layers. The classification layer of the CNN model built applies global average pooling which produces 2012 neurons that are directly connected to the last layer with the inception-v3 function. The accuracy of the results of the CNN model that was built succeeded in achieving an overall accuracy of 92.14% which was tested using 200 image data. The conclusion of this study is that the Convolutional Neural Network (CNN) algorithm that was built is relatively capable of diagnosing COVID-19 disease based on X-ray images of the lungs and the effectiveness of the model for diagnosing COVID-19 is lower than diagnosing diseases that are not infected with COVID-19. Keywords: Information System, Financial Management, Mosque. Abstrak - Covid-19 (Corona Virus Disease) wabah baru yang menular berasal dari Wuhan tahun 2019. Untuk mengetahui untuk mendiagnosis COVID-19 adalah dengan menganalisis citra X-ray paru-paru. Ahli medis menganalisa citra x-ray paru-paru untuk menetukan diagnosa, apakah covid atau normal. Hal ini sangat memakan waktu dan tidak efisien. Maka dari itu dibutuhkan teknologi yang dapat dengan cepat mendiagnosis penyakit tersebut. Convolutional Neural Network (CNN) dengan algorithma Logistic Regression merupakan salah satu pengembangan algoritma Multilayer Perceptron (MLP) yang di dirancang untuk mengidentifikasi berbagai pola gambar dari berbagai sisi. Model CNN yang dibangun pada penelitian ini memiliki 200 convolution layer dengan fungsi aktivasi ReLU, Batch Normalization, dan 5 max-pooling layer. Layer klasifikasi model CNN yang dibangun menerapkan global average pooling yang menghasilkan 2012 neuron yang langsung terhubung ke layer terakhir dengan fungsi inception-v3. Akurasi dari hasil model CNN yang dibangun berhasil mencapai keseluruhan akurasi 92,14% yang diuji menggunakan 200 data citra. Kesimpulan dari penelitian ini algoritma Convolutional Neural Network (CNN) yang dibangun relatif mampu mendiagnosis penyakit COVID-19 berdasarkan citra X-ray paru-paru dan tingkat efektivitas model mendiagnosis penyakit COVID-19 lebih rendah dibanding mendiagnosis penyakit yang tidak terjangkit COVID-19. Kata kunci : Klasifikasi, Covid-19, Logistic Regression, Convolutional Neural Networks, Inception